y is a sum of constants and so is itself a constant. Its derivative is, therefore, zero.
14x
There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).
if y=aex+be2x+ce3x then its derivative dy/dx or y' is: y'=aex+2be2x+3ce3x
Rprime= 2q + 2a + 3 Rdoubleprime= 4
y is a sum of constants and so is itself a constant. Its derivative is, therefore, zero.
x = 10x, so derivative = 10
14x
The first derivative is m and the second is 0 so the third is also 0.
Following the correct order of operations: derivative of x^2 + 6/2 = derivative of x^2 +3, which equals 2x
There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).
if y=aex+be2x+ce3x then its derivative dy/dx or y' is: y'=aex+2be2x+3ce3x
y"+y'=0 is a differential equation and mean the first derivative plus the second derivative =0.Look at e-x the first derivative is -e-xThe second derivative will be e-xThe sum will be 0
Rprime= 2q + 2a + 3 Rdoubleprime= 4
it is symmetric
y = x2 + 12x + 21At the max or min point, the first derivative of the function = 0.2x + 12 = 02x = -12x = -6
If dy/dx = (e) (9x) then Y = 4.5ex2 plus (any constant).==================================The above answer explains how to get the integral of e9x.If you were interested in how to get the derivative of e9x, the answer is e9.I suspect you may have actually wanted to ask how to get the derivative of e9x.In that case, the derivative of e9x is 9e9x.